Galvanic displacement assembly of ultrathin Co3O4 nanosheet arrays on nickel foam for a high-performance supercapacitor. (6th February 2017) - You, Yuxiu; Zheng, Maojun; Ma, Liguo; Yuan, Xiaoliang; Zhang, Bin; Li, Qiang; Wang, Faze; Song, Jingnan; Jiang, Dongkai; Liu, Pengjie; Ma, Li; Shen, Wenzhong
Abstract: High-performance supercapacitors are very desirable for many portable electronic devices, electric vehicles and high-power electronic devices. Herein, a facile and binder-free synthesis method, galvanic displacement of the precursor followed by heat treatment, is used to fabricate ultrathin Co3 O4 nanosheet arrays on nickel foam substrate. When used as a supercapacitor electrode the prepared Co3 O4 on nickel foam exhibits a maximum specific capacitance of 1095 F g −1 at a current density of 1 A g −1 and good cycling stability of 71% retention after 2000 cycling tests. This excellent electrochemical performance can be ascribed to the high specific surface area of each Co3 O4 nanosheet that comprises numerous nanoparticles.